Morocco -- Mind the Gap : Empowering Women for a More Open, Inclusive and Prosperous Society - World Bank (Washington, DC, 2015)
Morocco saw significant progress in terms economic, social and human development outcomes during the past decade. Women, as men, benefitted from such progress and increased access to services. Gender gaps in access to education narrowed significantly. The report recommends few key areas for strategic interventions. The recommendations are for the government and other development actors to focus on areas which are not only of greater potential impact but also a pre-requisite for women’s agency and empowerment. These include investment in women’s education (access and quality), the re-examination of certain discriminatory provisions in the country’s legal system (combined with an effort to strengthen implementation of the legislation and delivery of public sector services), and the promotion of cultural norms that value women as equal partners to men. The ultimate objective is to promote women’s empowerment as a means to achieve a more inclusive, open and prosperous society.